2006
DOI: 10.1111/j.1468-1331.2006.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of P300 in the recovery of post‐stroke global aphasia

Abstract: Seventeen right-handed patients suffering from global aphasia caused by a recent stroke in the left-hemisphere were studied. Passive P300 auditory event related potential paradigm was applied every months for 6 months. Aachen subtests were used for evaluating comprehension. Only a minority of the patients displayed the P300 at the baseline. Those patients had the best outcome at the Aachen comprehension subtest. Latency and amplitude changed over time in an unpredictable way. The number of patients presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Hence, our findings support further exploration using EEG simultaneously with robotics training to advance our understanding of CNS plasticity and to inform the design of more effective therapies to improve motor function following stroke [63][64][65][66][67]. However, our findings in this relatively brief robotics intervention are limited; future randomized clinical trials are needed to determine whether ankle robotics with versus without reward produces any durable, clinically meaningful mobility improvements in people with stroke.…”
Section: Discussionmentioning
confidence: 69%
“…Hence, our findings support further exploration using EEG simultaneously with robotics training to advance our understanding of CNS plasticity and to inform the design of more effective therapies to improve motor function following stroke [63][64][65][66][67]. However, our findings in this relatively brief robotics intervention are limited; future randomized clinical trials are needed to determine whether ankle robotics with versus without reward produces any durable, clinically meaningful mobility improvements in people with stroke.…”
Section: Discussionmentioning
confidence: 69%
“…Inclusion of a higher number of training sessions would have allowed for multiple P300 amplitude comparisons within the same presentation mode (cardboard vs. standard), an aspect to be addressed by future research. Nolfe et al (2006) measured the P300 in 17 patients with global aphasia in an auditory oddball paradigm and found those with the highest P300 amplitudes also showing best language abilities as measured with the Aachener Aphasia test (Huber et al, 1983). On the other hand, our TAP results clearly indicated attention deficits in all patients as they presented with very low PR in all measured categories, sometimes even results below PR1.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased P300 amplitudes were reported for patients diagnosed with left-hemispheric lesion and aphasia as compared to controls in a lexical semantic processing task (Hagoort et al, 1996). Nolfe et al (2006) found the P300 to be predictive of late recovery from aphasia. They judged the presence of the P300 amplitude to be indicative of preserved elementary cognitive function after stroke affecting areas that are relevant for language processing and production.…”
Section: Introductionmentioning
confidence: 99%
“…However, the neurophysiological correlates of auditory discrimination (MMN and P300) fluctuated throughout the intensive and conventional therapy blocks, yet a positive trend emerges when considering a longer timeframe. Thus, MMN and P300 seem worth including in a neurophysiological therapyoriented evaluation (Ilvonen et al, 2003;Nolfe et al, 2006).…”
Section: Effect Of Therapy Per Periodmentioning
confidence: 98%
“…Event-related potentials (ERPs) have shown great potential in characterising, evaluating, and monitoring language abilities in patients with aphasia. The pre-attentive mismatch negativity (MMN) (Näätänen, Gaillard, & Mäntysalo, 1978), the attentive P300 potential (Sutton, Braren, Zubin, & John, 1965), and the N400 potential (Kutas & Hillyard, 1980) are very suitable to evaluate phonological and lexical-semantic input processes during the course of aphasia recovery (Becker & Reinvang, 2007;Csépe, Osman-Sági, Molnár, & Gósy, 2001;Kawohl et al, 2010), as an amplitude re-enhancement can be associated with improvement of language functions over time, throughout the different recovery phases (Ilvonen et al, 2003;Nolfe, Cobianchi, Mossuto-Agatiello, & Giaquinto, 2006;Pulvermuller, Mohr, & Lutzenberger, 2004). Surprisingly, ERP studies measuring therapeutic effects on language abilities and its underlying reorganisation of neuronal circuits are scarce, and, to the best of our knowledge, to date have only been performed in patients with aphasia at least 1 year post-stroke.…”
Section: Introductionmentioning
confidence: 99%